Metal coating coated silicon-based material and secondary battery

By designing metal plating and ion adsorption layer on silicon-based materials, the problem of degradation of lithium-extraction window and cycling performance of silicon-based materials at large magnification is solved, and higher battery performance and longer life are achieved.

CN119419233AActive Publication Date: 2025-02-11ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
CN202411401351.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-11
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

Silicon-based materials are prone to side reactions when they come into contact with the electrolyte in lithium-ion batteries, resulting in a decrease in lithium-ion window and cycling performance at large magnification.

Method used

The metal plating is used to coat the silicon-based material. By designing the metal plating and ion adsorption layer on the surface of the silicon-based material, the electrolyte contact with the silicon-based material is reduced, the lithium ion precipitation is alleviated, and the fast charging capacity and cycle life of the battery are improved.

Benefits of technology

At large magnification, the lithium-ion window and cycling performance of silicon-based materials is significantly improved, the battery life is extended, and the battery safety and energy density is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005075361320000101
    Figure BDA0005075361320000101
  • Figure HDA0005075361330000011
    Figure HDA0005075361330000011
Patent Text Reader

Abstract

The invention discloses a metal coating coated silicon-based material and a secondary battery, and belongs to the technical field of lithium ion batteries. The silicon-based material comprises a silicon-based core structure, a metal coating structure and an ion adsorption layer structure, wherein the silicon-based inner core is positioned in the center of the silicon-based material; the metal coating structure covers the surface of the silicon-based core structure in a surrounding manner; the ion adsorption layer structure is located on the outer layer of the metal coating and covers the surface of the whole silicon-based material. The metal coating coated silicon-based material can reduce side reaction caused by contact between a silicon material and electrolyte, and still keeps a relatively good lithium precipitation window and cycle performance at a relatively high rate, so that the cycle life and the safety of a battery are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a metal-plated silicon-based material and a secondary battery. Background Art

[0002] Lithium-ion batteries have technical features such as high energy density and fast charging, and have been widely used in digital products and power supplies. With the continuous upgrading of technology, the energy density of lithium-ion batteries has reached its limit, and industrialized silicon negative electrode materials are being increasingly used in commercial lithium-ion batteries.

[0003] Silicon is a relatively active element that readily reacts with many compounds. It reacts with oxygen within milliseconds, forming a thin oxide film. It also reacts with the electrolyte in lithium-ion batteries within milliseconds. As silicon expands and contracts, cracks form in the SEI, leading to direct contact with the electrolyte. New SEI forms in these newly formed cracks. The SEI formation process competes with the direct chemical reaction between silicon and the electrolyte, and the contribution of each process depends on its kinetics and the concentration of lithium ions at the silicon / electrolyte interface. Direct contact between silicon and the electrolyte can produce side reactions, so a metal nanolayer deposited on the silicon surface can be used to minimize these side reactions.

[0004] Therefore, it is necessary to develop a silicon-based material that can reduce the side reactions occurring when silicon materials come into contact with the electrolyte, and still maintain good lithium deposition window cycle performance at a higher rate. Summary of the Invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a metal-coated silicon-based material that can reduce side reactions occurring when the silicon material contacts the electrolyte, while maintaining a good lithium deposition window and cycle performance at higher rates.

[0006] According to a first aspect of the present invention, a metal-coated silicon-based material is provided, wherein the silicon-based material comprises a silicon-based core structure, a metal-coated layer structure, and an ion adsorption layer structure;

[0007] The silicon-based core is located in the center of the silicon-based material; the metal coating structure surrounds and covers the surface of the silicon-based core structure; and the ion adsorption layer structure is located in the outer layer of the metal coating, covering the entire surface of the silicon-based material.

[0008] The metal coating layer covering the silicon-based material according to the first embodiment of the present invention has at least the following beneficial effects:

[0009] The metal-plated silicon-based material of the present invention can isolate the electrolyte accumulated on the surface of the material outside the metal plating layer through the metal plating designed on the outer layer when the battery is charged at a high rate, reduce the surface enrichment of ions on the negative electrode silicon particles, and alleviate the precipitation of lithium ions on the surface of the negative electrode sheet, thereby improving the fast charging capability of silicon and maintaining a good lithium precipitation window at a higher rate, solving the bottleneck of silicon use at a high rate.

[0010] The metal coating of the present invention coats the surface of the silicon-based material to construct a metal coating and an ion adsorption layer. Since silicon material itself is difficult for ions to embed, adding an ion adsorption layer makes it easier to absorb them into the interior of the silicon material; the ion adsorption layer is mainly responsible for adsorbing and releasing lithium ions during the charging and discharging process, and can more effectively manage the migration of lithium ions between the anode and cathode, thereby improving the charging and discharging efficiency and cycle life of the battery; the metal coating mainly plays the role of conductivity and structural support, which can enhance the conductivity of the silicon-based material, thereby improving the charging and discharging efficiency of the battery. At the same time, the metal coating can also buffer the volume change of the silicon-based material during the charging and discharging process to a certain extent, reduce structural damage, and extend the battery life.

[0011] The ion adsorption layer in the present invention is used in conjunction with the metal plating layer. The ion adsorption layer also prevents direct contact between the metal plating layer and the electrolyte, reducing unnecessary chemical reactions and protecting the internal structure of the battery. The metal plating layer and the ion adsorption layer work together to significantly improve the cycle life of the battery. The metal plating layer provides a stable structural foundation and excellent conductivity, while the ion adsorption layer optimizes the migration process of lithium ions. The combination of these two layers enables the anode to better adapt to volume changes during charging and discharging, reducing structural damage and thus improving the durability of the battery. The metal plating layer enhances conductivity and structural stability, while the ion adsorption layer optimizes the migration process of lithium ions. The two work together to significantly improve battery performance.

[0012] According to some embodiments of the present invention, the material of the silicon-based core structure includes at least one of silicon oxide particles, pre-lithiated silicon oxide particles, silicon nanowires, and silicon carbon particles.

[0013] Among them, the use of silicon material can far improve the energy density of the system than graphite.

[0014] According to some embodiments of the present invention, the metal type contained in the metal plating structure includes at least one of copper, gold, silver, bismuth, osmium, rhodium, palladium, and platinum.

[0015] Preferably, the metal contained in the metal plating structure is copper.

[0016] According to some embodiments of the present invention, the material of the ion adsorption layer structure includes at least one of nano-etherified cellulose, nano-esterified cellulose, nano-cellulose, nano-grafted cellulose, and nano-metal skeleton composite materials.

[0017] According to some embodiments of the present invention, the particle size of the silicon-based core structure is 5 to 20 μm.

[0018] According to some embodiments of the present invention, the silicon-based material has a silicon-based content of 1 to 15 wt %.

[0019] Preferably, the silicon-based content in the silicon-based material is 2-8 wt%.

[0020] More preferably, the silicon-based content in the silicon-based material is 3 wt%.

[0021] According to some embodiments of the present invention, the thickness of the metal plating structure is 2 to 20 nm.

[0022] Preferably, the thickness of the metal plating structure is 4-6 nm.

[0023] According to some embodiments of the present invention, the thickness of the ion adsorption layer structure is 250 to 600 nm.

[0024] Preferably, the thickness of the ion adsorption layer structure is 250-400 nm.

[0025] According to some embodiments of the present invention, the thickness of the ion adsorption layer (A) of the silicon-based material and the thickness of the metal plating layer (B) satisfy the relationship 60≥A / B≥40. For example, A / B can be 40, 50, or 60.

[0026] When A / B ≥ 60, the ion adsorption layer is too thick, the outer coating of silicon becomes less tight, and the structural stability is reduced. When A / B ≤ 40, the metal coating is too thick, while the ion adsorption layer is too thin, resulting in poor safety. Within the range of 60 ≥ A / B ≥ 40, the metal coating and ion adsorption layer work better together, resulting in better electrochemical performance.

[0027] In addition to improving cycle life, this composite anode structure may also bring other technical benefits. For example, by optimizing the material of the ion adsorption layer, the battery's energy density and power density can be increased. Furthermore, the combination of a metal plating layer and an ion adsorption layer may also improve battery safety, reducing the risk of overheating or short circuiting. By combining a metal plating layer and an ion adsorption layer, this secondary battery anode design not only improves the battery's cycle life but also may bring about technical improvements in energy density, power density, and safety.

[0028] According to some embodiments of the present invention, the method for preparing a metal coating comprises the following steps: immersing the silicon-based core structure in a metal pretreatment solution, adding a plating solution, and obtaining a metal-coated silicon-based material.

[0029] According to some embodiments of the present invention, the specific surface area of ​​the silicon-based material after metal plating is 1.5 to 3.5 m 2 / g.

[0030] The larger the specific surface area of ​​the silicon-based material, the more adsorption sites it provides, which is conducive to forming a more uniform adsorption layer and enhancing the tightness of the coating.

[0031] According to some embodiments of the present invention, the metal pretreatment solution includes a silver nitrate solution and a hydrofluoric acid solution.

[0032] The metal pretreatment solution is a mixed solution of silver nitrate and hydrofluoric acid. The silver nitrate and hydrofluoric acid work together to etch the silicon-based material, forming a silicon nanowire array on the surface of the silicon-based particles. In the subsequent heating and heating of the chemical copper plating process, the silicon nanowires will be embedded in the chemical copper plating layer, thereby improving the bonding force between the silicon and the metal plating layer, and effectively anchoring the metal plating layer firmly to the surface of the silicon particles. The metal plating is divided into a stage of etching the silicon-based material by silver nitrate and hydrofluoric acid, and a stage of chemical copper plating. By adjusting the concentration of the etchant, the silicon-based material is etched uniformly and fully. Then, the preparation temperature and preparation time of the chemical copper plating are controlled to ensure that the speed of the entire metal plating process is stable. In addition, the structure of the ion adsorption layer forms a uniform and dense metal plating layer and a tighter bond with the silicon-based material, which is beneficial to the continuity of the metal plating process and makes the coating uniform and dense.

[0033] According to some embodiments of the present invention, the chemical plating solution in the chemical copper plating stage is selected from at least one of copper sulfate and copper nitrate.

[0034] According to some embodiments of the present invention, the concentration of the silver nitrate solution is 0.01 to 0.03 mol / L.

[0035] Preferably, the concentration of the silver nitrate solution is 0.035-0.045 mol / L.

[0036] According to some embodiments of the present invention, the concentration of the hydrofluoric acid solution is 2 to 6 mol / L.

[0037] Preferably, the concentration of the hydrofluoric acid solution is 3 to 5 mol / L.

[0038] According to some embodiments of the present invention, the plating solution includes at least one of a sulfate, a nitrate or an acetate of a metal.

[0039] According to some embodiments of the present invention, the temperature for preparing the metal coating is 20-75°C.

[0040] Preferably, the temperature for preparing the metal coating is 25-50°C.

[0041] Appropriate temperature can promote the reduction and deposition of metal ions, forming a dense metal coating, which is conducive to the tight coating of the subsequent adsorption layer.

[0042] According to some embodiments of the present invention, the time for preparing the metal coating is 10 to 30 minutes.

[0043] Preferably, the time for preparing the metal coating is 15 to 25 minutes.

[0044] According to some embodiments of the present invention, the method for preparing the ion adsorption layer structure comprises the following steps:

[0045] An ion adsorption material solution is prepared, and the silicon-based material containing the metal coating is dispersed in the material solution of the ion adsorption layer to obtain a dispersion liquid, which is then dried to solidify the ion adsorption layer material and coat the surface of the silicon-based material containing the metal coating to form an ion adsorption layer structure.

[0046] According to a second aspect of the present invention, a negative electrode material for a lithium-ion battery is provided, comprising a negative electrode active material, a conductive agent and a binder; the negative electrode active material is composed of the above-mentioned metal-plated layer-coated silicon-based material.

[0047] According to a third aspect of the present invention, a secondary battery is provided, comprising a separator, an electrolyte, a positive electrode sheet, and a negative electrode sheet;

[0048] Wherein, the negative electrode plate comprises the metal-plated silicon-based material according to any one of claims 1 to 7.

[0049] The secondary battery according to the third embodiment of the present invention has at least the following beneficial effects:

[0050] The secondary battery described in the present invention is a silicon-based material constructed by constructing a metal plating layer and an ion adsorption layer in the material. The secondary battery has the characteristics of high energy fast charging and long cycle life.

[0051] According to some embodiments of the present invention, the cathode material is selected from LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiMnPO4, LiFePO4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.5 Co 0.2 Mn 0.3O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.6 Co 0.1 Mn 0.3 O2、LiNi 0.85 Co 0.15 Al 0.05 At least one of O2.

[0052] According to some embodiments of the present invention, the positive electrode current collector is aluminum foil.

[0053] According to some embodiments of the present invention, the negative electrode current collector is copper foil.

[0054] According to some embodiments of the present invention, the separator comprises at least one of polyethylene, polypropylene and polyvinylidene fluoride.

[0055] According to some embodiments of the present invention, the separator is provided between the positive electrode sheet and the negative electrode sheet.

[0056] According to some embodiments of the present invention, the electrolyte includes an electrolyte salt, an organic solvent, a positive electrode film-forming additive, a negative electrode film-forming additive, and a low-temperature additive.

[0057] The specific types and compositions of the electrolyte salt, organic solvent and additives in the present invention are not subject to specific restrictions.

[0058] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be obvious from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the following description of the embodiments with reference to the accompanying drawings, in which:

[0060] Figure 1 It is a schematic diagram of the structure of the metal coating coated silicon-based material described in the present invention. DETAILED DESCRIPTION

[0061] The embodiments of the present invention are described in detail below. The same or similar reference numerals throughout the embodiments represent the same or similar elements or elements with the same or similar functions. The embodiments described below are exemplary and are only used to explain the present invention and are not to be construed as limiting the present invention.

[0062] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0063] In the description of the present invention, it should be understood that descriptions involving orientation, such as the orientation or positional relationship indicated by up, down, etc., are based on the orientation or positional relationship shown in the embodiment, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0064] The terms "preferably," "more preferably," and the like, used herein refer to embodiments of the present invention that may provide certain benefits under certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. Furthermore, the recitation of one or more preferred embodiments does not imply that other embodiments are not useful, nor is it intended to exclude other embodiments from the scope of the present invention.

[0065] When a numerical range is disclosed herein, the range is considered continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe a feature or characteristic, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein are understood to include any and all subranges subsumed therein.

[0066] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts are within the scope of the present invention.

[0067] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0068] Example 1

[0069] This embodiment provides a secondary battery, which is composed of a separator, an electrolyte, a positive electrode plate and a negative electrode plate, wherein the negative electrode plate includes a metal-plated layer-coated silicon-based material.

[0070] The secondary battery of this embodiment is prepared by the following preparation method, which specifically includes the following steps:

[0071] 1) Positive electrode sheet: The active material LiCoO2, conductive agent acetylene black, conductive carbon nanotubes, and binder polyvinylidene fluoride (PVDF) are fully dispersed and evenly coated on the aluminum current collector in an N-methylpyrrolidone solvent system at a weight ratio of 98.2:0.5:0.3:1.0, and then cold-pressed and sliced ​​to obtain the positive electrode sheet.

[0072] 2) Negative Electrode: The negative electrode active material, conductive agent, and binder are mixed in a weight ratio of 97.2:0.5:2.3 to produce a negative electrode active material slurry. This is then cold-pressed and slit into negative electrode sheets. The silicon-based material content in the negative electrode active material is 3%. The metal-plated silicon-based material is designed as follows: the first component is pre-lithiated silicon oxide particles with a particle size of DV50 = 20 μm; the second component is a copper metallization layer with a thickness of 5 nm; and the third component is a nano-esterified cellulose material with an ion adsorption layer thickness of 250 nm. The chemical solution used to prepare the metallization layer has a silver nitrate concentration of 0.035 mol / L and a hydrofluoric acid concentration of 3 mol / L. The preparation temperature is 25°C and the preparation time is 15 minutes.

[0073] 3) Isolation membrane: The PE surface is coated with a ceramic mixture as an isolation membrane.

[0074] 4) Electrolyte: Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a volume ratio of 1:1:4:4, and then fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.

[0075] 5) Battery preparation: The positive electrode sheet, separator, and negative electrode sheet are wound or stacked to produce a bare cell, which is then packaged and injected with electrolyte to produce a finished lithium-ion battery.

[0076] Example 2

[0077] This embodiment provides a secondary battery, which is composed of a separator, an electrolyte, a positive electrode plate and a negative electrode plate, wherein the negative electrode plate includes a metal-plated layer-coated silicon-based material.

[0078] The secondary battery of this embodiment is prepared by the following preparation method, which specifically includes the following steps:

[0079] 1) Positive electrode sheet: The active material LiCoO2, conductive agent acetylene black, conductive carbon nanotubes, and binder polyvinylidene fluoride (PVDF) are fully dispersed and evenly coated on the aluminum current collector in an N-methylpyrrolidone solvent system at a weight ratio of 98.2:0.5:0.3:1.0, and then cold-pressed and sliced ​​to obtain the positive electrode sheet.

[0080] 2) Negative Electrode: The negative electrode active material, conductive agent, and binder are mixed in a weight ratio of 97.2:0.5:2.3 to produce a negative electrode active material slurry. This is then cold-pressed and slit into negative electrode sheets. The silicon-based material content in the negative electrode active material is 3%. The metal-plated silicon-based material is designed as follows: the first component consists of pre-lithiated silicon oxide particles with a particle size of DV50 = 20 μm; the second component consists of a copper metallization layer with a thickness of 10 nm; and the third component consists of a nano-esterified cellulose material with an ion adsorption layer thickness of 400 nm. The chemical solution used to prepare the metallization layer has a silver nitrate concentration of 0.035 mol / L and a hydrofluoric acid concentration of 5 mol / L. The preparation temperature is 35°C and the preparation time is 20 minutes.

[0081] 3) Isolation membrane: The PE surface is coated with a ceramic mixture as an isolation membrane.

[0082] 4) Electrolyte: Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a volume ratio of 1:1:4:4, and then fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.

[0083] 5) Battery preparation: The positive electrode sheet, separator, and negative electrode sheet are wound or stacked to produce a bare cell, which is then packaged and injected with electrolyte to produce a finished lithium-ion battery.

[0084] Example 3

[0085] This embodiment provides a secondary battery, which is composed of a separator, an electrolyte, a positive electrode plate and a negative electrode plate, wherein the negative electrode plate includes a metal-plated layer-coated silicon-based material.

[0086] The secondary battery of this embodiment is prepared by the following preparation method, which specifically includes the following steps:

[0087] 1) Positive electrode sheet: The active material LiCoO2, conductive agent acetylene black, conductive carbon nanotubes, and binder polyvinylidene fluoride (PVDF) are fully dispersed and evenly coated on the aluminum current collector in an N-methylpyrrolidone solvent system at a weight ratio of 98.2:0.5:0.3:1.0, and then cold-pressed and sliced ​​to obtain the positive electrode sheet.

[0088] 2) Negative Electrode: The negative electrode active material, conductive agent, and binder are mixed in a weight ratio of 97.2:0.5:2.3 to produce a negative electrode active material slurry, which is then cold-pressed and slit into negative electrode sheets. The silicon-based material content in the negative electrode active material is 3%. The metal coating coated with the silicon-based material meets the following design: the first component is silicon-carbon particles with a particle size of DV50 = 20 μm; the second component is a platinum metal coating with a thickness of 5 nm; and the third component is a nano-esterified cellulose material with an ion adsorption layer thickness of 250 nm. The chemical solution used to prepare the metal coating has a silver nitrate concentration of 0.035 mol / L and a hydrofluoric acid concentration of 3 mol / L. The preparation temperature is 25°C and the preparation time is 15 minutes.

[0089] 3) Isolation membrane: The PE surface is coated with a ceramic mixture as an isolation membrane.

[0090] 4) Electrolyte: Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a volume ratio of 1:1:4:4, and then fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.

[0091] 5) Battery preparation: The positive electrode sheet, separator, and negative electrode sheet are wound or stacked to produce a bare cell, which is then packaged and injected with electrolyte to produce a finished lithium-ion battery.

[0092] Example 4

[0093] This embodiment provides a secondary battery, which is composed of a separator, an electrolyte, a positive electrode plate and a negative electrode plate, wherein the negative electrode plate includes a metal-plated layer-coated silicon-based material.

[0094] The secondary battery of this embodiment is prepared by the following preparation method, which specifically includes the following steps:

[0095] 1) Positive electrode sheet: The active material LiCoO2, conductive agent acetylene black, conductive carbon nanotubes, and binder polyvinylidene fluoride (PVDF) are fully dispersed and evenly coated on the aluminum current collector in an N-methylpyrrolidone solvent system at a weight ratio of 98.2:0.5:0.3:1.0, and then cold-pressed and sliced ​​to obtain the positive electrode sheet.

[0096] 2) Negative Electrode: The negative electrode active material, conductive agent, and binder are mixed in a weight ratio of 97.2:0.5:2.3 to produce a negative electrode active material slurry. This is then cold-pressed and slit into negative electrode sheets. The silicon-based material content in the negative electrode active material is 3%. The metal coating coated with the silicon-based material meets the following design requirements: the first component is silicon nanowires with a particle size of DV50 = 20 μm; the second component is a platinum metal coating with a thickness of 10 nm; and the third component is a nano-esterified cellulose material with an ion adsorption layer with a thickness of 400 nm. The chemical solution used to prepare the metal coating has a silver nitrate concentration of 0.035 mol / L and a hydrofluoric acid concentration of 5 mol / L. The preparation temperature is 35°C and the preparation time is 20 minutes.

[0097] 3) Isolation membrane: The PE surface is coated with a ceramic mixture as an isolation membrane.

[0098] 4) Electrolyte: Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a volume ratio of 1:1:4:4, and then fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.

[0099] 5) Battery preparation: The positive electrode sheet, separator, and negative electrode sheet are wound or stacked to produce a bare cell, which is then packaged and injected with electrolyte to produce a finished lithium-ion battery.

[0100] Comparative Example 1

[0101] This comparative example provides a secondary battery, which is composed of a separator, an electrolyte, a positive electrode plate and a negative electrode plate, wherein the negative electrode plate comprises a metal-plated layer-coated silicon-based material.

[0102] The difference between this comparative example and Example 1 is that the negative electrode sheet is different.

[0103] The negative electrode sheet of this comparative example includes the following preparation steps:

[0104] The negative electrode active material, conductive agent, and binder are mixed in a weight ratio of 97.2:0.5:2.3 to produce a negative electrode active material slurry. This slurry is then cold-pressed and slit to produce negative electrode sheets. The silicon-based material contains 3% silicon nanowires. The silicon-based material meets the following design requirements: the first component is silicon nanowires; the second component is a copper metallization layer with a thickness of 15 nm; and the third component is a nano-esterified cellulose material with an ion adsorption layer with a thickness of 300 nm. The chemical solution used to prepare the metallization layer has a silver nitrate concentration of 0.06 mol / L and a hydrofluoric acid concentration of 6 mol / L. The preparation temperature is 45°C and the preparation time is 35 minutes.

[0105] Comparative Example 2

[0106] This comparative example provides a secondary battery, which is composed of a separator, an electrolyte, a positive electrode plate and a negative electrode plate, wherein the negative electrode plate comprises a metal-plated layer-coated silicon-based material.

[0107] The difference between this comparative example and Example 1 is that the negative electrode sheet is different.

[0108] The negative electrode sheet of this comparative example includes the following preparation steps:

[0109] The negative electrode active material, conductive agent, and binder are mixed in a weight ratio of 97.2:0.5:2.3 to produce a negative electrode active material slurry, which is then cold-pressed and slit into negative electrode sheets. The silicon-based material content in the negative electrode active material is 3%. The silicon-based material meets the following design requirements: the first component is silicon nanowires; the second component is a platinum metal coating with a thickness of 40nm; and the third component is a nano-esterified cellulose material with an ion adsorption layer with a thickness of 400nm. The chemical solution used to prepare the metal coating has a silver nitrate concentration of 0.06mol / L and a hydrofluoric acid concentration of 6mol / L. The preparation temperature is 50°C and the preparation time is 40 minutes.

[0110] Comparative Example 3

[0111] This comparative example provides a secondary battery, which is composed of a separator, an electrolyte, a positive electrode plate and a negative electrode plate, wherein the negative electrode plate comprises a silicon-based material.

[0112] The difference from Example 1 is that the metal of the metal plating layer is nickel.

[0113] Comparative Example 4

[0114] This comparative example provides a secondary battery, which is composed of a separator, an electrolyte, a positive electrode plate and a negative electrode plate, wherein the negative electrode plate comprises a silicon-based material.

[0115] The difference from Example 1 is that no ion adsorption layer is included.

[0116] Comparative Example 5

[0117] This comparative example provides a secondary battery, which is composed of a separator, an electrolyte, a positive electrode plate and a negative electrode plate, wherein the negative electrode plate comprises a silicon-based material.

[0118] The difference from Example 1 is that no metal plating is performed.

[0119] Comparative Example 6

[0120] This comparative example provides a secondary battery, which is composed of a separator, an electrolyte, a positive electrode plate and a negative electrode plate, wherein the negative electrode plate comprises a silicon-based material.

[0121] The difference from Example 1 is that the ion adsorption layer is adsorption carbon fiber.

[0122] Comparative Example 7

[0123] This comparative example provides a secondary battery, which is composed of a separator, an electrolyte, a positive electrode plate and a negative electrode plate, wherein the negative electrode plate comprises a silicon-based material.

[0124] The difference from Example 1 is that the thickness of the metal plating layer is 25 nm, and the thickness of the ion adsorption layer is 600 nm.

[0125] Test Case

[0126] The secondary batteries described in Examples 1 to 4 and Comparative Examples 1 to 2 were subjected to performance tests.

[0127] The rate window is measured by charging to 4.2V at 2.0C, 2.2C, 2.4C, 2.6C, 2.8C, 3.0C, and 3.2C, charging to the cut-off voltage at a rate of 1.5C, and cycling for 20 weeks without lithium deposition.

[0128] The cycle retention rate is the percentage of the initial capacity after the cell is charged to 4.2V at 2.8C step rate and charged to the cut-off voltage at 1.8C for 800 cycles.

[0129] The expansion rate is the percentage of the initial thickness of the node thickness after the battery cell is charged to 4.2V at a 2.8C step rate and charged to the cut-off voltage at a conversion rate of 1.8C for 100 cycles.

[0130] The power density calculation formula is: battery capacity * voltage platform / cell size (cell length * width * thickness); cycle life in this article refers to the number of cycles the battery cell can cycle when the capacity retention rate after the battery cycle is less than 60%.

[0131] The most significant safety performance test is the thermal shock test: thermal shock means taking three battery cells and keeping them at a certain temperature in an incubator for a certain period of time. The battery cells must pass the test without explosion, fire, or breakage of the tabs. The thermal shock condition in this article is to fully charge the battery to 100% SOC at 0.5C constant current and constant voltage, and keep it at 132℃ for 60 minutes. The passing condition is that the battery cells have good appearance, no electrolyte leakage, explosion, or fire. If the three battery cells meet the conditions, it will be a 3 / 3 pass.

[0132] Table 1 Performance parameters of secondary batteries of Examples 1 to 4 and Comparative Examples 1 to 7

[0133]

[0134] According to the above test results, the secondary batteries of Examples 1 to 4 of the present invention have good cycle retention and low expansion rate. Compared with Examples 3 and 4 of the present invention, the metal coating of Examples 1 and 2 is preferably copper. Under the coating thickness specified by the present invention, the rate window and cycle retention are optimal, which significantly improves the electrical performance of the lithium-ion battery. The silver nitrate concentration and hydrofluoric acid concentration in Comparative Examples 1 and 2 are not within the scope of the present invention. The battery exhibits lithium plating and rapid decay of cycle capacity under high-rate charge and discharge conditions. The reason is that the influencing factors of each stage of the metal plating are superimposed. In the early stage, the etching effect of silver nitrate and hydrofluoric acid on silicon nanowires is too strong, and the nanowire array is too dense. The preparation temperature and time of the latter are too long, which accelerates the rate of chemical copper plating. The whole process changes nonlinearly, which reduces the continuity of the copper plating process, resulting in weak bonding between the silicon substrate and the chemical plating layer. As a result, lithium plating and rapid decay of cycle capacity occur under high-rate charge and discharge conditions. The experimental results of Comparative Examples 4 and 5 demonstrate that the silicon-based core structure, metal coating structure, and ion adsorption layer structure of the metal-coated coating material described herein work synergistically, maintaining a good lithium deposition window and cycling performance at higher rates. In Comparative Example 5, when only the ion adsorption layer is used, the contact between the ion adsorption layer and silicon is not as close as the contact between silicon and the metal coating, and a small amount of silicon still contacts the electrolyte, resulting in high gas production and poor thermal conductivity. Comparative Examples 6 and 7 demonstrate that materials with other ion adsorption layer structures and parameters outside the specified range exhibit extremely poor cycling capacity retention.

[0135] While the embodiments of the present invention have been described in detail above, the present invention is not limited to the embodiments described above. Various modifications may be made within the scope of knowledge possessed by a person skilled in the art without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof may be combined with one another unless there is a conflict.

Claims

1. A metal-plated silicon-based material, characterized in that: The silicon-based material comprises a silicon-based core structure, a metal coating structure and an ion adsorption layer structure; The silicon-based core is located at the center of the silicon-based material; the metal coating structure surrounds and covers the surface of the silicon-based core structure; and the ion adsorption layer structure is located in the outer layer of the metal coating, covering the entire surface of the silicon-based material.

2. The metal-plated silicon-based material according to claim 1, characterized in that: The material of the silicon-based core structure includes at least one of silicon oxide particles, pre-lithiated silicon oxide particles, silicon nanowires, and silicon carbon particles; preferably, the metal types contained in the metal plating structure include at least one of copper, gold, silver, bismuth, osmium, rhodium, palladium, and platinum; preferably, the material of the ion adsorption layer structure includes at least one of nano-etherified cellulose, nano-esterified cellulose, nano-cellulose, nano-grafted cellulose, and nano-metal skeleton composite materials.

3. The metal-plated silicon-based material according to claim 1, characterized in that: The Dv50 particle size of the material in the silicon-based core structure is 5 to 50 μm; preferably, the silicon-based content in the silicon-based material is 1 to 15 wt%; preferably, the thickness of the metal plating structure is 2 to 20 nm; preferably, the thickness of the ion adsorption layer structure is 250 to 600 nm; Preferably, the thickness A of the ion adsorption layer and the thickness B of the metal plating layer are: 60≥A / B≥40.

4. The metal-plated silicon-based material according to claim 1, characterized in that: The method for preparing the metal plating structure comprises the following steps: immersing the silicon-based core structure in a metal pretreatment solution, adding a plating solution, and obtaining a silicon-based material after metal plating; preferably, the method for preparing the ion adsorption layer structure comprises the following steps: dispersing the silicon-based material after metal plating in a material solution of the ion adsorption layer to obtain a dispersion, and drying the dispersion to solidify the ion adsorption layer material and coat the surface of the silicon-based material after metal plating to form an ion adsorption layer structure.

5. The metal-plated silicon-based material according to claim 4, characterized in that: The specific surface area of ​​the silicon-based material after metal plating is 1.5 to 3.5 m 2 / g.

6. The metal-plated silicon-based material according to claim 4, characterized in that: The metal pretreatment solution includes a silver nitrate solution and a hydrofluoric acid solution; preferably, the concentration of the silver nitrate solution is 0.01 to 0.03 mol / L; preferably, the concentration of the hydrofluoric acid solution is 2 to 6 mol / L; preferably, the plating solution includes at least one of metal sulfates, nitrates or acetates.

7. The metal-plated silicon-based material according to claim 4, characterized in that: The temperature for preparing the metal coating is 20-75° C.; preferably, the time for preparing the metal coating is 10-30 minutes.

8. A negative electrode material for a lithium ion battery, characterized in that: The negative electrode material of the lithium ion battery comprises a negative electrode active material, a conductive agent and a binder; Wherein, the negative electrode active material comprises the metal-plated silicon-based material as claimed in any one of claims 1 to 7.

9. The negative electrode material for lithium-ion batteries according to claim 8, characterized in that: The content of the metal-plated silicon-based material in the negative electrode active material is 1 wt % to 15 wt %.

10. A secondary battery, characterized in that: The secondary battery comprises a separator, an electrolyte, a positive electrode sheet and a negative electrode sheet; Wherein, the negative electrode plate comprises the metal-plated silicon-based material as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Etched silicon structures, method of forming etched silicon structures and uses thereof

    CN103988342A

  • Manufacturing method and application of amino functional silicon-based negative electrode materials

    CN104009213A

  • Nanocellulose-silicon-graphite micron sheet flexible electrode material and preparation method and application thereof,

    CN110581267A

  • Positive electrode material for flexible lithium ion battery and preparation method and application thereof and flexible lithium ion battery

    CN110581278A

  • Dendritic aqueous binder, negative electrode pole piece and battery, and preparation methods thereof

    CN112159638A